(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
The determination of curve generation rules for the body features is the lynchpin in the creation of computer generated three dimensional (3D) lower body human mannequins. In this paper, methods to determine the characteristic features of the curves, such as the waist curve, abdomen curve and hip curve were analyzed as a precursor to creating female lower body 3D mannequins. Methods to generate the profile curves for the different body features were devised by adding insertion points onto the curves. The relationships between the coordinates of the insertion points and body measurement data were analyzed using SPSS software and rules for the generation of curves for each of the featured parts were determined. Subsequently these were used to provide the basis for the creation of a female lower body 3D mannequin, which can be useful for the further development of clothing e-commerce. The modelling system was developed by automatically extracting anthropometric data from a non- contact 2D anthropometry system (photographs) and used to generate human models according to their different body features. The system can facilitate the interactive design of different fashion styles and the automatic generation of garment patterns.